A comprehensive assessment of the antioxidant capacity and sensory properties of wheat-based cereal breads produced in different formulations - Arslan Burnaz, Nesibe; Hendek Ertop, Müge; Baltacı, Cemalettin (Harran Tarim ve Gida Dergisi, 2025)
In this study, it was aimed to investigate the physicochemical, sensory and antioxidant properties of some wheat-based cereal bread types that are offered for sale and frequently consumed in the markets in Turkey. Bread types were produced with the help of a home-type bread-making machine, and 100% white wheat flour bread (WB) was used as a control. Sensory evaluations were determined by using the nine-point hedonic scale method. Total phenolic contents were determined by using Folin-Ciocalteau’s method. Antioxidant capacities were determined by using ABTS, DPPH, and FRAP assays. Besides, all data were evaluated by using principal component analysis (PCA) to discriminate the properties of bread types. Whole-wheat bread showed the highest antioxidant potentials (200.00µM TEAC for ABTS, 147.50µM TEAC for DPPH, 116.94µM TEAC for FRAP) and the highest amount of phenolic content (64.30mg GAE/100gDW), but a low overall acceptability score (6.00/9.00). As a result, the addition of wheat-based cereal flours affected the antioxidant, sensory, and physical properties of the produced breads (p<0.05). Different cereal flours added to the bread formulation positively affected the antioxidant properties of all breads, but only wheat bran and oat flour addition positively affected the overall sensory acceptability of the bread types. Hereby this study, individuals will be made aware of consuming bread types enriched with different cereal flours including important micronutrients instead of WB which is so poor in micronutrients. The study also provides convenience to individuals in the production of these breads in a home-type bread-making machine. This study reveals the various data for functional properties of bread types that are consumed less than WB.